Interventions to improve district-level routine health data in low-income and middle-income countries: a systematic review - Lee, J; Lynch, CA; Hashiguchi, LO; Snow, RW; Herz, ND; Webster, J; Parkhurst, J; Erondu, NA (BMJ Publishing Group, 2021)
Background: Routine health information system(s) (RHIS) facilitate the collection of health data at all levels of the health system allowing estimates of disease prevalence, treatment and preventive intervention coverage, and risk factors to guide disease control strategies. This core health system pillar remains underdeveloped in many low-income and middle-income countries. Efforts to improve RHIS data coverage, quality and timeliness were launched over 10 years ago.